Future Challenges in Crop Protection Against Fungal Pathogens - Goyal, Aakash; Manoharachary, Chakravarthula (Springer eBooks, 2014)
This volume presents the issues and challenges of crop pathogens and plant protection. Composed of the latest knowledge in plant pathology, the book covers topics such as fungal diseases of the groundnut, plant growth promoting rhizobacteria, plant pathogenic fungi in the genomics era, the increased virulence of wheat rusts, and oat fungal diseases. Written by experienced and internationally recognized scientists in the field, Future Challenges in Crop Protection Against Fungal Pathogens is a concise yet comprehensive resource valuable for both novice as well as experienced plant scientists and researchers.